Real-world data on canine chronic kidney disease in Greece: clinical and quality of life insights - Chortara, Ioulia; Tsokana, Constantina N.; Pavlidou, Eleni; Sandri, Thaisa L.; Wright, Andrea; Valiakos, George (Frontiers in Veterinary Science, 2025)
IntroductionChronic Kidney Disease (CKD) is an important health concern in dogs, characterized by structural and functional kidney abnormalities persisting for over three months. Despite being significant for dog health and commonly managed by veterinarians, there is a lack of real-world data (RWD) on canine CKD (cCKD) worldwide. This study aimed to address this gap by collecting and analyzing RWD on cCKD cases from Greece.MethodsAn observational study was conducted across Greece from January to October 2023. Data were collected from 215 dogs diagnosed with cCKD, staged according to the International Renal Interest Society (IRIS) criteria. Veterinarians and owners completed detailed forms capturing clinical, demographic, and Quality of Life (QoL) information. Laboratory analyses included serum biochemistry and urinalysis. Canine QoL was assessed using the VetMetrica™ health-related quality of life (HRQL) instrument. Statistical analyses were performed to identify trends and correlations.ResultsMost cases (79.6%) were classified as early IRIS stages (1 and 2) and 20.5% in advanced stages (3 and 4). Smaller sized dogs and mixed breeds represent approximately 50 and 38% of the enrolled cases, respectively. Mean age of cCKD diagnosis was 10.7 years. Statistical analysis showed that larger-sized dogs develop CKD at younger ages and approximately one quarter of reported cases fall below the geriatric age. Common comorbidities included cardiovascular (28.8%), periodontal (26.5%), degenerative joint disease (18.1%), and liver disease (17.2%) which had a significant impact on the QoL of the animal even in early IRIS stages. Clinical signs such as polyuria, vomiting, diarrhea and halitosis were more prevalent in cases with advanced IRIS stages and were reported as troublesome by owners.ConclusionThis study provides valuable RWD on cCKD in Greece, highlighting the importance of early detection and comprehensive management, as it can lead to more effective treatment plans, reduce the disease progression, and ultimately improve the overall well-being of the dogs. Moreover, data analysis demonstrates the significance of comorbidities and their impact on the QoL of a dog with cCKD; addressing comorbidities early, longevity and quality of life for canine companions can be enhanced. Future research should expand on these insights to enhance global understanding and management of cCKD.